Impact of COVID-19 on Immunization Services for Maternal and Infant Vaccines: Results of a Survey Conducted by Imprint—The Immunising Pregnant Women and Infants Network - Anja Saso; Helen Skirrow; Beate Kampmann (Vaccines, 2020)
The COVID-19 pandemic response has caused disruption to healthcare services globally, including to routine immunizations. To understand immunization service interruptions specifically for maternal, neonatal and infant vaccines, we captured the local experiences of members of the Immunising Pregnant Women and Infants Network (IMPRINT) by conducting an online survey over 2-weeks in April 2020. IMPRINT is a global network of clinicians and scientists working in maternal and neonatal vaccinology. The survey included discrete questions to quantify the extent of disruption as well as free-text options to explore the reasons behind reported disruptions. Of the 48 responses received, the majority (75%) were from low-and-middle-income countries (LMICs). Of all respondents, 50% or more reported issues with vaccine delivery within their country. Thematic analysis identified three key themes behind immunization disruption: “access” issues, e.g., logistical barriers, “provider” issues, e.g., staff shortages and user “concern” about attending immunization appointments due to COVID-19 fear. Access and provider issues were more commonly reported by LMIC respondents. Overall, respondents reported uncertainty among parents and healthcare providers regarding routine immunization. We conclude that further quantification of routine vaccination disruption is needed, alongside health service prioritization, logistical support and targeted communication strategies to reinforce routine immunizations during the COVID-19 response.